2019
DOI: 10.3390/min9120782
|View full text |Cite
|
Sign up to set email alerts
|

Surface Properties and Floatability Comparison of Aegirite and Specularite by Density Functional Theory Study and Experiment

Abstract: Understanding the differences in surface properties between aegirite and specularite is of great significance to study their separation. In this work, the surface properties of aegirite and specularite, as well as their relationships to floatability, have been explored by first principle calculation, flotation, and Zeta potential measurement. The surface relaxation indicated that the specularite (001) surface appeared to show more surface reconstruction. The unsatisfied bond properties, Mulliken bond populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The fact that the theoretical value of γ for augite calculated using Eq. ( 11) is nearly identical to the surface energy value of 1.2 J m -2 reported for aegirine (Li et al, 2019) give us confidence about the reliability of our calculation method. Note that augite and aegirine are isostructural and form a solid solution, so it is not unexpected for their surface energy values to be very similar.…”
Section: Effect Of Reaction-driven Fracturingsupporting
confidence: 86%
“…The fact that the theoretical value of γ for augite calculated using Eq. ( 11) is nearly identical to the surface energy value of 1.2 J m -2 reported for aegirine (Li et al, 2019) give us confidence about the reliability of our calculation method. Note that augite and aegirine are isostructural and form a solid solution, so it is not unexpected for their surface energy values to be very similar.…”
Section: Effect Of Reaction-driven Fracturingsupporting
confidence: 86%
“…The unit cell parameters were a = b = 5.03 Å, c = 13.75 Å, α = β = 90 • , and γ = 120 • . Li et al [27] studied the surface energy of several specularite crystal surfaces through DFT calculations, and the results showed that the (0 0 1) surface of specularite has the lowest surface energy. Therefore, the (0 0 1) surface was constructed according to the overall structure of specularite.…”
Section: Computational Detailsmentioning
confidence: 99%
“…18 The (001) surface was the most stable surface of chlorite and specularite, which was modelled for further adsorption calculation. 7,19 The bottom atoms xed mineral face was geometry optimized using the smart algorithm method under 0.001 kcal mol À1 convergence accuracy. The Ewald summation procession was applied to calculate van der Waals force and electrostatic energy.…”
Section: Microotation Experimentsmentioning
confidence: 99%
“…It is difficult to separate in mineral processing due to the existence of the iron element in iron-containing silicates and iron ores, which leads to similar magnetic and oatability properties of targeted minerals and gangues. 6,7 It has been proven that the chlorite depressed by starch could not be oated effectively in reverse otation route using anionic collector sodium oleate, and the addition of sodium alginate could improve the separation efficiency. 8 Besides, the sodium oleate also is invalid for the separation of hematite and aegirite; for example, the recovery of aegirite maintained around 80% while hematite around 90% with sodium oleate 1 Â 10 À4 mol L À1 at pH ¼ 4-9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation